The peculiarities of the functional state of the liver under conditions of skeletal trauma, thermal burns of the skin and their combinations in the period of later manifestations of traumatic disease in the experiment - Kashchak, T. V.; Dzetsiukh, T. I.; Uhlyar, U. V. (Journal of Education, Health and Sport, 2019)
Aim: To find out the peculiarities of the functional state of the liver under conditions of skeletal trauma, thermal burns of the skin and their combination in the period of late manifestations of traumatic disease in the experiment. Materials and methods. 60 non-linear white male rats weighing 180-200 g were used in the experiments. In thiopentalonate sodium (40 mg / kg-1) in the first experimental group (24 animals), a skeletal injury was simulated by applying a metered impact to each thigh, which caused their closed fracture. In the second experimental group (30 animals) simulated skin burns III A-B degree 10-11% of the surface of the body - to the depilated surface of the back was applied copper plate of 28 cm2, pre-immersed in boiling water for 3-5 minutes. In the third experimental group (30 animals), the two lesions were combined. The control group was a group of intact animals (6 animals). After 14, 21, and 28 days after injury in thiopental-sodium (60 mg • kg-1 mass) conditions, in 6 animals of each experimental group studied the bile-forming function of the liver by catheterization of the common bile duct and bile intake for 1 hour. In the obtained bile was determined by the concentration of total bile acids, cholesterol, conjugated bilirubin. The cholate-cholesterol coefficient and the degree of conjugation of bilirubin were calculated. From the experiment, animals were removed after bile sampling by total bloodletting from the heart. Results. Under the influence of simulated injuries during the late manifestations of traumatic disease, there was a violation of the bile function of the liver, as evidenced by a decrease in the concentration in the bile of total bile acids, conjugated bilirubin and the degree of its conjugation. The development of liver dysfunction depended on the type of trauma. Against the background of the skeletal injury, the indicators reached their minimum level up to 21 days and up to 28 days - they returned to normal. Under thermal burns of the skin after 14 days, the violation of the studied parameters was greater than after a skeletal injury. In the future, the indicators grew, but up to 28 days did not reach the level of control. The greatest violations were noted after applying a combined injury, starting from 21 days of the experiment. Their recovery is slower. The indicated dynamics of the content of total bile acids and cholesterol led to an increase in the lithogenic properties of bile, as evidenced by a decrease in the cholesterol-cholesterol index. The rate was the smallest up to 28 days in conditions of thermal burn of the skin and combined injury. Conclusion. In the period of late manifestations of traumatic disease, there is a violation of the functional state of the liver, which dominates in conditions of combined trauma from 21 days does not subside until 28 days of the experiment.